Neuroprotective Effects of Berberine After Severe Traumatic Brain Injury in Male Rats: The Role of IL-1β and IL 10 - Siavash Anbai; Farzin Niazi; Ali Siahposht-Khachaki; Labkhand Sefidari; Davood Farzin (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Traumatic brain injury (TBI) is the leading cause of death in young people. Berberine is a flavonoid rich in barberries and many traditional Iranian herbal remedies that could be used in treatment of neurodegenerative diseases. These properties make it a viable treatment for neurodegenerative diseases. Therefore, this study intended to investigate the neuroprotective activity of berberine in animal model of traumatic brain injury. Materials and methods: Thirty minutes after induction of traumatic brain injury by Marmarou free fall method, Wistar rats received berberine (10, 20 and 50mg/kg i.p.). Cerebrospinal fluid (CSF) was collected from cisterna magna after behavioral tests to evaluate the levels of a proinflammatory cytokine (IL-1β) and anti-inflammatory cytokine (IL-10). Results: According to current results, TBI can cause decline in Veterinary coma scale, cerebral edema, Blood-Brain Barrier dysfunction, vesibulomotor impairment, and alteration of cytokines in favor of inflammation in CSF. Nevertheless, administration of berberine in 10 and 20mg/kg can attenuate these findings. Also, beberine (20 mg/kg) effectively increased IL-10 and decreased IL-1β in CSF. All findings were more noticeable at 20mg/kg berberine (P < 0.001). Conclusion: Our study showed that berberine had neuroprotective effects on the brain and was able to affect the consequences of brain trauma. Also, it is suggested that at least some of these neuroprotective effects are mediated by modulation in the path of inflammatory factors in the brain.